An Analysis of Positive Politeness Strategy Used In "Up" Movie - Isthi Mawar Thoyyibah; Lina Tri Astuty Beru Sembiring; Merry Rullyanti (Literary Criticism, 2021)
This research is entitled "An Analysis of Positive Politeness Strategies used in "UP" movie. It aims at finding the kinds of politeness strategies and context produced in "UP" movie. The researcher used qualitative research since the data engaged are displayed in the form of strings of words. The data were collected from a movie "UP" which was realesed in 2010. Analysis of this research is focused on the utterances produced by the character in Up movie. Using the theory of Brown and Levinson (1987), there are 15 strategies in positive politeness, they are 1) notice, attend to the hearer (his interest, wants, needs, goods); 2) exaggerate (interest, approval, sympathy with the hearer); 3) intensify interest to the hearer: 4) use in-group identity markers; 5) seek agreement; 6) avoid disagreement; 7)presuppose/ raise/ assert common ground; 8) joke; 9) assert or presuppose the speaker's knowledge and concern for the hearer's wants; 10) offer/promise; 11) be optimistic; 12) include both the speaker and the hearer in the activity; 13) give (or ask for) reasons; 14) assume or assert reciprocity; 15) and give gifts to the hearer (goods, sympathy, understanding, cooperation). The result shows that the character produced the highest number of positive politeness in the utterances that found in strategy 4: Use in group identity markers. Context of positive politeness strategy also using Brown and Levinson theory where 9 from 15 context theory found in the utterance. The result shows that the character produced the highest number of contexts of positive politeness in the utterances that found in give association clue context Keyword: Movie, Positive Politeness strategy and context, Utterances.